2013
DOI: 10.1371/journal.pone.0056032
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Infection Patterns Since Birth and Risk of Severe Malaria: A Nested Case-Control Study in Children on the Coast of Kenya

Abstract: Children in malaria endemic areas acquire immunity to severe malaria faster than to mild malaria. Only a minority of children suffers from severe malaria and it is not known what determines this. The aim of this study was to establish how P. falciparum infections during the first years of life affect the risk of severe malaria. A matched case-control study was nested within a large birth cohort set up to study the immunoepidemiology of pneumococci on the Kenyan coast. Infection patterns in three-monthly blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 27 publications
2
16
0
3
Order By: Relevance
“…This finding is consistent with previous observations that genetically-diverse infections in children are associated with an increased risk of malaria [ 15 , 41 , 42 ]. We have previously shown that genetically-diverse infections are more often present in young children who develop severe non-cerebral malaria compared to age- and location-matched children [ 43 ]. Taken together with the antibody data presented here, these findings suggest that the genetic diversity of asymptomatic infections in young children is a marker of the intensity of exposure to the parasite at a time when anti-merozoite antibodies have not attained concentrations required for protection against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous observations that genetically-diverse infections in children are associated with an increased risk of malaria [ 15 , 41 , 42 ]. We have previously shown that genetically-diverse infections are more often present in young children who develop severe non-cerebral malaria compared to age- and location-matched children [ 43 ]. Taken together with the antibody data presented here, these findings suggest that the genetic diversity of asymptomatic infections in young children is a marker of the intensity of exposure to the parasite at a time when anti-merozoite antibodies have not attained concentrations required for protection against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the study cohort has been provided elsewhere ( 48 ). Briefly, children born at KCH or attending its vaccination clinic during the first month of life were recruited into a longitudinal birth cohort (Kilifi Birth Cohort [KBC]) linked to the KHDSS to evaluate the risk factors for invasive pneumococcal disease in young children.…”
Section: Methodsmentioning
confidence: 99%
“…The answer is not clear as determining the risk of severe malaria in relationship to infections requires large cohorts to capture the relatively rare cases of severe disease and such studies have simply not been done. However, a recent nested case control study in Kenya provided evidence that children who suffer severe malaria do not have fewer infections early in life as compared to community controls (156). Cerebral malaria is rare in very young children in areas of high year round transmission suggesting that immunity to cerebral malaria is acquired early under the cover of passively acquired maternal antibodies (157).…”
Section: Human Immunity and Malariamentioning
confidence: 99%